The Changing Historiography of the Moynihan Report - Kooken, Jason (The Toro Historical Review, 2023)
This paper discusses the ways that historians have studied and discussed the Moynihan Report throughout the decades following its release to the public, and how the interpretations and conversations regarding the document have changed over time.